Design, construction, and performance evaluation of a gari roaster. Issue 3 (6th October 2016) - Sobowale, Sunday Samuel; Adebiyi, Janet Adeyinka; Adebo, Oluwafemi Ayodeji
Abstract: Traditional roasting of cassava mash into gari continues to be an arduous and intricate unit operation for processors. It is highly labor intensive, tedious, unhygienic, and productivity is often too low to justify labor and investment time. The aim of this study was thus to design and fabricate a gari roaster and evaluate its performance. Cassava mash of different moisture contents (36.21, 39.44, and 43.27%) were roasted at different garifying temperatures (75, 85, and 95°C) and performance characteristics including, roasting time, percentage material loss, functional efficiency, throughput, and machine capacity were evaluated. Results obtained indicated that roasting cassava mash of 39.44% at 85°C yielded the best roasting conditions, as it had the least material loss of 7.8%, best throughput capacity and functional efficiency of 34.66 kg/hr and 92.20%, respectively. The fabricated gari roaster does not require skilled labor and can effectively address the challenges associated with gari roasting. Practical Application: The fabricated roaster is relevant to the roasting of cassava mash to produce gari . This will practically address the impending challenges associated with gari roasting especially in the rural areas. This roaster will further ensure production of quality gari to its teeming consumers, thereby contributing to food security.